The top performers in vocational training - Stamm, Margrit [Verfasser]; Niederhauser, Michael [Verfasser]; Kost, Jakob [Verfasser] (My University, 2010)
"In the course of a Swiss longitudinal study on the training paths of particularly able adolescents in the Swiss vocational training system, it became apparent that the 'talent pool' (adolescents with above-average talents) had been overtaken by the 'comparison group' (those with average talents). This surprising fact constitutes the starting point of the current article. Based on the question of who the top performers are, the article seeks to identify their characteristics and derives a set of predictors with which success in vocational training can be predicted. On the whole, the results indicate that training success is only attributable to general talent characteristics to a very limited extent, and is rather much more strongly based on behavioural characteristics and company-based standards. However, both behavioural characteristics and company-based standards can be moulded and supported. The results form an empirically grounded foundation for the promotion of gifted trainees in companies providing vocational training." (Autorenreferat, BIBB-Doku)
Keywords: P 2.3 Auszubildende; P 1.9 Begabte; G 1.2.3.1 Potenziale; T 1.1 Empirische Berufsbildungsforschung; I 2.2.1 Westeuropa; Begabungsforschung; Auszubildender; Begabter; Leistungsverhalten; Leistungsmotivation; Begabtenförderung; Empirische Untersuchung; Längsschnittuntersuchung; Einflussfaktor; Persönlichkeitsmerkmal; Interkulturelle Faktoren; Schweiz; 2004-2008